Menjangkau Kelompok Rentan di Desa Terpencil - Beatriks Novianti Kiling-Bunga; Indra Yohanes Kiling (Universitas Nusa Cendana, 2019)
International Non Governmental Organization (INGO) works to support community in needs either in urban or rural setting. One of the main target group is the most vulnerable group in a community. This group were often left out and not involved in community empowerment projects implemented. This article aims to describe the condition of a vulnerable group located at Ongulero village, Sigi district, Central Sulawesi Province, and to recommend an intervention that could be applied by stakeholders in that village. Situation description were done in a narrative form, strengthen by observation and interview data that was analysed in psychological context. Result of the analysis shows that this vulnerable group was yet to be reached by community empowerment program that was being applied by an INGO there. Children are part of a vulnerable group that is when empowered and facilitated, could become a solution for community empowerment. A potential intervention is discussed further in this article to help improve child participation in Ongulero village.